Dispersed Behavior and Perceptions in Assortative Societies - Frick, Mira; Iijima, Ryota; Ishii, Yuhta (American Economic Review, 2022)
We formulate a model of social interactions and misinferences by agents who neglect assortativity in their society, mistakenly believing that they interact with a representative sample of the population. A key component of our approach is the interplay between this bias and agents’ strategic incentives. We highlight a mechanism through which assortativity neglect, combined with strategic complementarities in agents’ behavior, drives up action dispersion in society (e.g., socioeconomic disparities in education investment). We also suggest that the combination of assortativity neglect and strategic incentives may be relevant in understanding empirically documented misperceptions of income inequality and political attitude polarization. (JEL C78, D11, D31, D72, D82, D91)